Respiratory tract infections and risk factors for infection in a cohort of 330 patients with axial spondyloarthritis or psoriatic arthritis - Frede, Natalie; Rieger, Eva; Lorenzetti, Raquel; Nieters, Alexandra; Venhoff, Ana C.; Hentze, Carolin; von Deimling, Marcus; Bartholomä, Nora; Thiel, Jens; Voll, Reinhard E.; Venhoff, Nils (Frontiers in Immunology, 2022)
Respiratory tract infections (RTIs) are the most common infections in patients with rheumatic diseases under immunosuppressive treatment and may contribute to morbidity and mortality as well as increased healthcare costs. However, to date only limited data on infection risk in spondyloarthritis (SpA) patients are available. In this study we assessed the occurrence of respiratory tract infections in a monocentric real-world cohort consisting of 330 patients (168 psoriatic arthritis and 162 axial spondyloarthritis patients) and determined factors associated with increased infection risk. Out of 330 SpA patients, 89.3% had suffered from ≥ 1 upper respiratory tract infection (URTI) and 31.1% from ≥ 1 lower respiratory tract infection (LRTI) within the last two years. The most common URTIs were rhinitis and laryngitis/pharyngitis with 87.3% and 36.1%, respectively. Bronchitis constituted the most common LRTI, reported in 29.7% of patients. In a multivariate binomial logistic regression model occurrence of LRTI was associated with chronic lung disease (OR 17.44, p=0.006), glucocorticoid therapy (OR 9.24, p=0.012), previous history of severe airway infections (OR 6.82, p=0.013), and number of previous biological therapies (OR 1.72, p=0.017), whereas HLA B27 positivity was negatively associated (OR 0.29, p=0.025). Female patients reported significantly more LRTIs than male patients (p=0.006) and had a higher rate of antibiotic therapy (p=0.009). There were no significant differences between axSpA and PsA patients regarding infection frequency or antibiotic use. 45.4% of patients had required antibiotics for respiratory tract infections. Antibiotic therapy was associated with smoking (OR 3.40, p=0.008), biological therapy (OR 3.38, p=0.004), sleep quality (OR 1.13, p<0.001) and age (OR 0.96, p=0.030). Hypogammaglobulinemia (IgG<7g/l) was rare (3.4%) in this SpA cohort despite continuous immunomodulatory treatment. Awareness of these risk factors will assist physicians to identify patients with an increased infection risk, who will benefit from additional preventive measures, such as vaccination and smoking cessation or adjustment of DMARD therapy.